If it's not what You are looking for type in the equation solver your own equation and let us solve it.
26x+43=5(8x+3)
We move all terms to the left:
26x+43-(5(8x+3))=0
We calculate terms in parentheses: -(5(8x+3)), so:We get rid of parentheses
5(8x+3)
We multiply parentheses
40x+15
Back to the equation:
-(40x+15)
26x-40x-15+43=0
We add all the numbers together, and all the variables
-14x+28=0
We move all terms containing x to the left, all other terms to the right
-14x=-28
x=-28/-14
x=+2
| 12d-4=-7 | | -4x+5=-4x-4−4x+5=−4x−4 | | z÷10-1=5 | | x=90-(4x+12) | | n/4=12n= | | 4(v-1)=-9v-30 | | x=90-(4+12) | | 5(v+8)-8v=28 | | v/2-15=21 | | 3y-2=6(y-1)-3y | | 69.6=6(m+3.2 | | 8n=-40n= | | 14=-8u+2(u-8) | | 6x−6=15x+15 | | 105.3=9(m+2.9) | | -1z+5=7 | | 4x/2+10/5=20 | | 20w+100=400 | | 15=x/3=8 | | 72=6(m+3.7) | | −75x+57=−75x+57 | | -24=-6p/7 | | 10+200+10x=1000-69x | | 4n-7=5n | | 5−6(x+4)=15 | | 1768=34(p+10) | | 2x2-22=50;6 | | 1/6(6x-18)=-3 | | 2/5(15x+10)-3x=3x-4+8 | | -(5x+4)-5=-4x-(x+9) | | 5n-12=n | | 20x+30=120 |